1976
DOI: 10.1136/pgmj.52.613.678
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged nasogastric tube feeding in critically ill and surgical patients

Abstract: Fifteen patients with varying diagnoses were fed via nasogastric tubes for between 7 and 41 days using a feed consisting of Caloreen (a glucose polymer) and Albumaid (a beef serum hydrolysate) with vitamin and mineral supplements. The feed proved nutritionally adequate and relatively free of complications. Diarrhoea was seen only in those patients receiving antibiotics by the nasogastric route. Codeine phosphate abolished this symptom in all patients. The constant drip method of administration proved efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Hypernatraemia can also occur and is usually due to excess water loss or transient diabetes insipidus in neurosurgical patients. 97 Between 10% and 30% of tube fed patients are hyperglycaemic 96 and may need oral antidiabetic agents or insulin, before and during feeding. Rebound hypoglycaemia may also occur in tube fed patients if feeding is stopped abruptly, especially if they are on antidiabetic therapy.…”
Section: Metabolic Complications Of Etfmentioning
confidence: 99%
“…Hypernatraemia can also occur and is usually due to excess water loss or transient diabetes insipidus in neurosurgical patients. 97 Between 10% and 30% of tube fed patients are hyperglycaemic 96 and may need oral antidiabetic agents or insulin, before and during feeding. Rebound hypoglycaemia may also occur in tube fed patients if feeding is stopped abruptly, especially if they are on antidiabetic therapy.…”
Section: Metabolic Complications Of Etfmentioning
confidence: 99%
“…46 Patients receiving artificial support should be monitored closely as a result, and because of the risk of developing refeeding syndrome. 2 Generally haematological and biochemical parameters should be measured before introducing nutritional support.…”
Section: Aspirationmentioning
confidence: 99%
“…(1981) reported that all incidences of hypernatraemia, hyponatraemia, hyperkalaemia and hypokalaemia could have arisen as complications of enteral tube feeding in various patients with cerebrovascular accident (CVA), organic brain syndrome, cancer, infectious disease, respiratory failure, trauma, renal insufficiency, Hodgkins’ lymphomas, drug overdose, or hip fracture. On the contrary, Woolfson et al. (1976) concluded that none of these complications was attributable to enteral tube feeding in patients with mouth surgery, crushed chest, head injury, postoperative collapse, or respiratory failure.…”
Section: Introductionmentioning
confidence: 99%